Zoonotic Diseases in India: A Growing Concern - Mamata Panda (Pediatric Infectious Disease)
Zoonotic diseases are on the rise globally as well as in India. Out of 1,407 human pathogens, 816 were zoonotic. Out of them, 538 were bacterial and Rickettsial, 317 fungi, 208 viruses, 287 helminths, and 57 protozoal. Thirteen percent of total pathogens were emerging or reemerging, and 75% of these were classified as zoonoses. Usually, emerging infections are more challenging and threatening to humans as little knowledge is acquired about them. Examples of some of these in recent times include COVID-19, Ebola hemorrhagic fever, Zika virus, and Nipah virus. Emerging infections have a chance to spread across countries due to international travel. India is primarily an agriculture-dependent country. Animals play an important role in boosting the economy of India. It is a developing country with poor resources. Some of the key factors that play a crucial role in the surge of zoonotic diseases are: dense population, industrialization, urbanization, deforestation, and domestication of animals. These factors lead to increased animal and human contacts. Besides, factors like poor sanitation, insufficient health infrastructure, and lack of health education are also responsible. The recent COVID-19 pandemic was a big challenge to our healthcare system.